Exposure of tungsten heavy alloys at high thermal loads in LHD - Chandra Prakash Dhard; Suguru Masuzaki; Dirk Naujoks; Rudolf Neu; Daisuke Nagata; Mikhail Khokhlov (Nuclear Materials and Energy, 2024)
Tungsten has been considered a plasma-facing material in a future fusion reactor because of its low sputtering yield and low fuel retention. It has been examined in several tokamaks. In stellarators, it has recently been used for some plasma-facing components. However, in addition to its high cost, W is difficult to machine due to its hardness and brittleness and therefore alternative materials in the form of tungsten heavy alloys are being investigated and some tests have already been performed in the ASDEX upgrade [1]. WNiFe materials are magnetic, but since magnetization saturates at ∼ 2 Tesla for W97NiFe [1], these could also be investigated for use in stellarators. Samples were prepared from pure W, W95NiCu, W97NiFe and W95NiFe alloys. The samples were exposed in the Large Helical Device (LHD) stellarator during three recent operation campaigns. The samples were inserted by means of the divertor manipulator at the positions of the strike line under H-, D- and He plasma conditions. These experiments were designed to test the samples at high thermal loads by adjusting the exposure conditions to achieve sample temperatures above, around and below the melting temperatures of Ni, Fe and Cu. During some of these exposures, although the temperatures reached above the melting limit, resulting in segregation of Ni, Fe and Cu and partial release of alloying materials, normal plasma operation continued without any radiative collapse. Scanning electron microscopy with focused ion beam (SEM/FIB), energy dispersive X-ray spectroscopy (EDX) and glow discharge optical emission spectroscopy (GDOES) measurements confirmed the observed change in surface morphology.